Analysis of Nahwu Learning Progress in Indonesian Universities Based on the Character of Value Concerns - Rahmat, Agus Salam; Abdurrahman, Maman (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: Historically, Arabic learning in Indonesia made a significant progress at the end of 1990s to the beginning of 2000s. This study was according to the importance of âNahwuâ and presence of the subject which exclusively taught about âNahwuâ after educational institutions effectively taught their students about Arabic subject itself. This situation happened in several universities in Indonesia with an Arabic language program, whether it is an educational program or Arabic literature program. The main purposes of this study were: knowing about âNahwuâ learning contents in several universities; finding out âNahwuâ learning implementations in several universities; and knowing âNahwuâ learning character of value progress in several universities. This study has been implemented in several universities in Indonesia which had subject curriculum of âNahwuâ learning. The sample of this study was taken by using the purposive sampling method. Based on any considerations from the time, academic, and curriculum concerns, the sample was taken from several universities which stand on Java, they were: UPI (Indonesia University of Education) in Bandung, UI (University of Indonesia) in Jakarta, UIN (State Islamic University) Syarif Hidayatullah in Jakarta, UIN Sunan Gunung Djati in Bandung, UGM (Gadjah Mada University) in Yogyakarta, UNPAD (Padjadjaran University) in Bandung, and UNINUS (Archipelago Islamic University) in Bandung. The result of this study was about basic concept of âNahwuâ learning contents, which were taught in university and âNahwuâ learning in university included the character of value based learning.KEY WORDS: Nahwu; University; Character; Value; Arabic Learning. Â About the Authors: Dr. H. Agus Salam Rahmat is a Senior Lecturer at the Department of Arabic Language Education, Faculty of Language and Literature Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. Prof. Dr. H. Maman Abdurrahman is Head of Study Program of Arabic Language Education SPs UPI (School of Postgraduate, Indonesia University of Education) in Bandung, West Java, Indonesia. For academic interests, the authors are able to be contacted via their e-mails at: asr.syamsudin@gmail.com and mamanabdurrahman@upi.eduHow to cite this article? Rahmat, Agus Salam & Maman Abdurrahman. (2017). âAnalysis of Nahwu Learning Progress in Indonesian Universities Based on the Character of Value Concernsâ in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.189-202. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (January 28, 2017); Revised (March 2, 2017); and Published (April 28, 2017).